A field condition–based test method for artificially frozen soils. Issue 1 (15th December 2018) - Zhao, Xiaodong; Wu, Yue; Lai, Zejin; Zhou, Guoqing
Abstract : The formation process of artificially frozen soils in the field, which significantly affects the behaviors of frozen walls, can be divided into three stages, i.e., K 0 drained consolidation ( K 0 DC), drained freezing under applied stress (F), and the formation of lateral thermal gradient (G). The K 0 DCGF method was thus developed and its reliability was comprehensively evaluated by testing on hollow cylindrical specimens. It was found that the measured K 0 at the inner and outer surfaces of the hollow cylindrical specimens was identical to that of the cylindrical specimens. Unlike the widely observed frost heave during freezing prior to stress application, drained freezing under applied stress resulted in a slight shrinkage of the specimen's volume. The weakening of the lateral thermal gradient on the K 0 DCGF–based strength was smaller than that observed in previous studies of frozen soil specimens with a vertical thermal gradient because of the parallel structures of the frozen zones with different temperatures in the frozen hollow cylinder. The proposed K 0 DCGF method was validated using multiple tests and can be used for assessing the strength behavior and associated mechanism of various artificially frozen soils.